*Problem 3.13 (a) Prove the following commutator identity: [AB, C] = A[B. C]+[A. C]B. [3.64] (b) Show that [x". p] = ihnx"-!. (c) Show more generally that [f(x), p] = ih- dx [3.65] for any function f(x).
*Problem 3.13 (a) Prove the following commutator identity: [AB, C] = A[B. C]+[A. C]B. [3.64] (b) Show that [x". p] = ihnx"-!. (c) Show more generally that [f(x), p] = ih- dx [3.65] for any function f(x).
Related questions
Question
![*Problem 3.13
(a) Prove the following comnutator identity:
[AB, C] = A[B, C]+[A. C]B.
[3.64]
(b) Show that
[x". p] = ihnx"-1.
%3D
(c) Show more generally that
[f (x), p] = ih
dx
[3.65]
for any function f(x).](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fdfdff23b-e68a-49d1-884e-503136b21f33%2F91a21b51-0b7c-4202-89dd-b0804d7aa55d%2Ffe1jdcc_processed.jpeg&w=3840&q=75)
Transcribed Image Text:*Problem 3.13
(a) Prove the following comnutator identity:
[AB, C] = A[B, C]+[A. C]B.
[3.64]
(b) Show that
[x". p] = ihnx"-1.
%3D
(c) Show more generally that
[f (x), p] = ih
dx
[3.65]
for any function f(x).
Expert Solution

This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
This is a popular solution!
Trending now
This is a popular solution!
Step by step
Solved in 3 steps with 2 images
